Republic of Croatia : 2017 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for the Republic of Croatia. - International Monetary Fund. European Dept. (Washington, D.C. : International Monetary Fund, 2018)
This 2017 Article IV Consultation highlights that Croatia continued its third year of positive economic growth in 2017. Growth is expected to stay at similar levels in the near future but to decelerate over the medium term. Consumer prices increased at a moderate pace and wage growth was also moderate as unemployment remained high. The external current account is expected to record another strong surplus, underpinned by robust performance of exports and tourism and lower repatriation of profits as banks absorbed losses from Agrokor. The balance of risks has improved but vulnerabilities remain sizable as public and external debt levels are still high, and the full impact of the Agrokor restructuring is yet unknown.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet